Administrative empowerment among middle school principals in Wasit Governorate from the teachers’ point of view - عبد الرزاق غفوري حيدر (Journal of College of Education, 2021)
The current research aims to identify the degree of administrative empowerment, and the current research has identified male and female educational teachers who practice the teaching profession in middle schools in Wasit Governorate for the academic year (2019-2020), and the current study sample consisted of (300) teachers and schools chosen from the community The original is for teachers in preparatory schools in the General Directorate of Education in Wasit Governorate, which number (654) teachers and schools, and the researcher used a set of appropriate statistical means to reach the results required in the research procedures, and the current research reached the following results: • Male and female teachers in Wasit governorate do not enjoy a good level of administrative empowerment. • There are no statistically significant differences in the scale of administrative empowerment for (males, females(. The researcher developed a set of recommendations and proposals based on the results of the current research.